Parallel processor [community service]. - Aaronson, L. (IEEE spectrum)
This paper relates how IBM senior technical staff member, Sandra Johnson, was able to parlay her expertise into two successful careers: one as an architect of computing systems and the other as an energetic volunteer who introduces women, minorities and youngsters to technology. While heading a small business technology group and contributing to a company-wide technical leadership team, Johnson serves on the board of directors of the Austin Area Urban League, raising scholarship funds with her sorority, and co-chairing Black Family Technology Awareness Week, an international event of which IBM is a major sponsor.